Global transcriptome characterization and assembly of the thermophilic ascomycete Chaetomium thermophilum - Singh, Amit; Schermann, Géza; Reislöhner, Sven; Kellner, Nikola; Hurt, Ed; Brunner, Michael (Genes, 2021)
A correct genome annotation is fundamental for research in the field of molecular and structural biology. The annotation of the reference genome of Chaetomium thermophilum has been reported previously, but it is essentially limited to open reading frames (ORFs) of protein coding genes and contains only a few noncoding transcripts. In this study, we identified and annotated full-length transcripts of C. thermophilum by deep RNA sequencing. We annotated 7044 coding genes and 4567 noncoding genes. Astonishingly, 23% of the coding genes are alternatively spliced. We identified 679 novel coding genes as well as 2878 novel noncoding genes and corrected the structural organization of more than 50% of the previously annotated genes. Furthermore, we substantially extended the Gene Ontology (GO) and Enzyme Commission (EC) lists, which provide comprehensive search tools for potential industrial applications and basic research. The identified novel transcripts and improved annotation will help to understand the gene regulatory landscape in C. thermophilum. The analysis pipeline developed here can be used to build transcriptome assemblies and identify coding and noncoding RNAs of other species.